Vascular Flora of Punta Arenas City: Comparative Analysis of Composition, Life Forms, and Biogeographic Origins - Castro-Morales, S (BioMed Central Ltd, 2024)
The composition of the vascular flora in Punta Arenas city, found in the city’s public spaces, was studied. The species were identified and recorded in a database, which was supplemented with information on taxonomic classification, growth habit, Raunkiaer’s life form, origin status (native or exotic), and original continent-level distribution. These data were compared with studies conducted in five other cities in central Chile, together with an analysis of compositional similarity with these cities, by using the additive complement of Simpson’s index (1– βsim). In Punta Arenas, 119 species were identified, showing a higher proportion of Gymnosperms compared to central Chilean cities. The most represented families were Asteraceae (16 species), Fabaceae (14), Rosaceae (14), Poaceae (12), and Pinaceae (10), which together accounted for 55% of the floristic richness. The compositional similarity between Punta Arenas and the other central Chilean cities ranged from 0.187 to 0.315, showing lower similarity than expected by chance (Montecarlo randomization test; P < 0.05). The primary origin distribution of Punta Arenas’ vascular flora was European, unlike central Chilean cities where it was Asian. Finally, the proportion of exotic species (91.6%) and the number of exotic species per native species (16 exotics/native) were the highest documented for cities in Chile and higher than in other 114 cities worldwide. These results indicate that Punta Arenas’ urban flora differs from the flora in central Chilean cities, not only in taxonomic composition but also in growth habit, biogeographical origin, and high level of exoticism. These differences are likely due to the city’s territorial isolation and extreme southern location (53°S), leading to a unique urban flora configuration. © The Author(s) 2024.